GENETIC IMPROVEMENT OF ETTAWA SENDURO GOAT BY USING ARTIFICIAL INSEMINATION (AI) AND TRAINING COURSE OF MILK PROCESSING AT LUMAJANG DISTRICT - Pratiwi Trisunuwati (Journal of Innovation and Applied Technology, 2017)
The objective of this study was to disseminate the technology of Artificial Insemiation (AI) and Milk Processing. This activity expected to help the Ettawa goat farmer to overcoming their problems which subsequently it can be improve theirincome.The methods use dinthisstudywastogiveinsightknowledgeandsimpletechnologytotheselectedEttawa goat partner group. Based on the discussion with Etawa goat partner group, several activities were carried out, i.e.: (1) to improve  good genetic quality of Etawa goat  livestocks, (2) providing milk technology product such as yogurt and kefir  (3)provide assistance of  cup sealer,(4)trainingofproductionandfinancialmanagement,(5)provide training artificial insemination. The result of this study showed that the Ettawa goat farmer as partner group  receive the strengthening  of their business. Such as adopted the techniqueofselectingsuperiorsires,livestock management,recycling of  manure  as a fertilizerproduction, milk technology production plant. .